Peran Pendidikan Terhadap Etika Penggunaan Informasi Dan Komunikasi Abad 21 - Muhammad Dafa Lubis; Muhammad Irwan Padli Nasution (CV. ITTC INDONESIA, 2024)
Science and technology have advanced and developed very rapidly in the twenty-first century. The way we learn now is not the same as before. Standards are ignored when learning is carried out, even though these standards are now an important guide to achieving learning goals. This study looks at how education in schools influences the use of ICT in the 21st century using qualitative methodology and a literature review. ICT Ethics is a set of morals, procedures, (customs, etiquette), values ​​about right and wrong, as well as ICT rights and obligations that a group or society adheres to in using information technology devices for data collection, data storage and information display. public. . The traditional classroom learning paradigm, which views students as passive consumers of information, can be replaced with a paradigm where students actively seek knowledge by using ICT in the learning process.